1983
DOI: 10.1104/pp.72.1.186
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cyanide Content and Linamarase Activity in Wounded Cassava Roots

Abstract: When cassava (Mauihet escadeta Crantz) root was cut into blocks and incubated under laboratory conditions, the blocks showed more widespread and more even symptoms of physiological deterioration than those under natural conditins. Thus, the tissue block system has potental for bio- (12)(13)(14). The deterioration consists of two types. The first is physiological deterioration characterized by internal root discoloration. The second is microbial deterioration caused largely by a wound pathogen (1). The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…We established that the total cyanide content was high in the cortex and decreased sharply towards the center of the root in each variety. These results are complied with those achieved by [29,25] who showed that along the proximal to the distal end, the cyanide content decreases sharply. Our results suggest that it is safe to remove or exclude the cortex portion before eating the root.…”
Section: Total Cyanide Contents In Cassava Slices (1/4 1/2 3/4) Andsupporting
confidence: 80%
“…We established that the total cyanide content was high in the cortex and decreased sharply towards the center of the root in each variety. These results are complied with those achieved by [29,25] who showed that along the proximal to the distal end, the cyanide content decreases sharply. Our results suggest that it is safe to remove or exclude the cortex portion before eating the root.…”
Section: Total Cyanide Contents In Cassava Slices (1/4 1/2 3/4) Andsupporting
confidence: 80%
“…1 was further confirmed by immunoblotting after two-dimensional SDS-PAGE (Fig. 4) (13). In common with linamarases from Phaseolus lunatus and Trifolium repens (6,11), cassava linamarase resides in the cell wall (20).…”
Section: But Left Peptidementioning
confidence: 85%
“…Therefore, it is generally assumed that these cyanogens and their catabolic enzymes are localized in the intact plant in different compartments and come into contact with each other upon tissue disruption. Although only limited information is currently available, examples of compartmentation at both tissue and subcellular levels are known (13,14). To broaden our knowledge of how compartmentation normally prevents premature and suicidal cyanogenesis in undamaged plants, our laboratory is investigating the mature seeds of black cherry (Prunus serotina Ehrh.)…”
mentioning
confidence: 99%
“…By 6) were subjected to SDS-PAGE. Proteins were either stained by Brilliant Blue G-Colloidal (lanes 1-3) or electroblotted onto nitrocellulose and immunodecorated with affinity purified anti-AH antiserum (lanes [4][5][6]. B, Aliquots (7.5 contrast, PH was absent from the more internal procambial cells, including those housing AH, and from the bundle sheath and cotyledonary storage parenchyma.…”
Section: Immunolocalization Of Ah and Ph By Light Microscopymentioning
confidence: 99%
“…It is therefore assumed that amygdalin and its catabolic enzymes are kept separate in undamaged cherry seeds by some means of compartmentation (15). In sorghum leaves, premature cyanogenesis is prevented by compartmentation at the tissue level (7), whereas subcellular compartmentation seems more likely in other vegetative systems (2,6,13). How cyanogenic seed tissues, such as those found in Prunus species, prevent untimely HCN release remains largely unknown (19).…”
mentioning
confidence: 99%